2017
DOI: 10.2174/2468187307666170906150731
|View full text |Cite
|
Sign up to set email alerts
|

Early Stages of Antibacterial Damage of Metallic Nanoparticles by TEM and STEM-HAADF

Abstract: Background: Propagation of pathogens has considered an important health care problem due to their resistance against conventional antibiotics. The recent challenge involves the design of functional alternatives such as nanomaterials, used as antibacterial agents. Early stages of antibacterial damage caused by metallic nanoparticles (NPs) were studied by Transmission Electron Microscopy (TEM) and combined Scanning Transmission Electron Microscopy with High Angle Annular Dark Field (STEM-HAADF), aiming to contri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…The disintegration of the cell wall and the release of substances were identified through TEM images, so Ag NPs proved to be toxic for both bacteria [ 62 ]. España-Sánchez et al [ 63 ] studied, through the HRTEM technique, the contact realized between spherical Ag NPs and Pseudomonas aeruginosa bacteria. The images proved that Ag NPs agglomerate at the bacterial wall, eventually causing disruption and internalization.…”
Section: Silver Nanoparticles—overview and Synthesis Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The disintegration of the cell wall and the release of substances were identified through TEM images, so Ag NPs proved to be toxic for both bacteria [ 62 ]. España-Sánchez et al [ 63 ] studied, through the HRTEM technique, the contact realized between spherical Ag NPs and Pseudomonas aeruginosa bacteria. The images proved that Ag NPs agglomerate at the bacterial wall, eventually causing disruption and internalization.…”
Section: Silver Nanoparticles—overview and Synthesis Methodsmentioning
confidence: 99%
“…The images proved that Ag NPs agglomerate at the bacterial wall, eventually causing disruption and internalization. The diffusion of Ag NPs is increased within this penetration so that bacterial death is completed [ 63 ]. This mechanism seems to be more expressed in the case of Gram-negative bacteria.…”
Section: Silver Nanoparticles—overview and Synthesis Methodsmentioning
confidence: 99%
“…Even though some alteration to the structure of the SDSD VSD22 cells after treatment were observed ( Figure 6 ), these did not affect the growth of this strain. Untreated cells exhibited a uniform cytoplasm, while aggregation of the cytoplasmic components was observed among treated cells (see Figure 6C ; España-Sánchez et al, 2017 ). It has been suggested that these cytoplasmic alterations might be associated to some degree of damage to the cell membrane ( Dakal et al, 2016 ; Wang et al, 2016 ).…”
Section: Resultsmentioning
confidence: 94%
“…After the interaction, an aliquot (50 µL) was plated in Mueller Hinton plates and incubated for 16 h at 37 °C. In three independent experiments, duplicated survival bacterial recovery (antibacterial activity, AA) was calculated according to our previous work (España-Sánchez et al, 2018).…”
Section: Antibacterial Activity Of Cunps Against P Aeruginosamentioning
confidence: 99%